Predictors of long‐term outcome after septal myectomy in symptomatic hypertrophic obstructive cardiomyopathy patients with previous alcohol septal ablation and residual obstruction. Issue 7 (21st May 2019) - Zhu, Changsheng; Tang, Bing; Cui, Hao; Wang, Shengwei; Xiao, Minghu; Chen, Zixian; Meng, Yanhai; Zhao, Shihua; Song, Yunhu; Yu, Qinjun; Wang, Shuiyun
Abstract: Background and aim: Recently alcohol septal ablation (ASA) has emerged as an alternative treatment for drug‐refractory hypertrophic obstructive cardiomyopathy (HOCM) and a subgroup of HOCM patients with previous ASA may need myectomy. However, subsequent outcome and mechanism of residual obstruction has not been determined. This study aims to determine outcome after myectomy and mechanism of residual obstruction in HOCM patients with previous ASA. Methods: From February 2009 to June 2017, 38 HOCM patients with previous ASA underwent surgical septal myectomy at our institution. Seventy‐six patients who underwent surgical septal myectomy initially were included as the comparison group through one‐to‐two propensity score matching method. Results: Fourteen available cardiac magnetic resonance images revealed inferior location and small area of infarcted myocardium induced by ASA in 12 patients and outside targeted location in two patients. During follow‐up (median, 2.4; maximum, 7.8 years), event‐free survival at 7 years was 83.2% in the previous ASA group and 94.6% in the comparison group, respectively ( P  = 0.0378). Multivariable analysis indicated previous ASA (hazard ratio, 4.28; 95% confidence intervals [CI], 1.20‐15.26; P  = 0.025) and postoperative left ventricular end‐diastolic diameter (hazard ratio, 1.14; 95% CI, 1.05‐1.23; P  = 0.002) were independent predictors of adverse events. Conclusions: This study demonstrated that uncontrollable extent and location of infarcted myocardium induced by ASA may attribute to residual obstruction after previous ASA, and the long‐term event‐free survival after myectomy was inferior. It may provide special precaution to patient selection and the increased number of ASA practiced worldwide.